Integration of Youth into the labor Market for Combating Youth Unemployment: A European Perspective - MD Habibur Rahman; Brelyantika Indra Jesa (Politeknik Kesejahteraan Sosial Bandung, 2023)
Young people's integration in European countries into the job market has become a serious societal issue, owing to its long-term influence on life prospects. However, the overall increase in youth unemployment concerns the European Union (EU), which has initiated several youth-specific policy measures in the previous decade. Integrating young people into the labor market is a priority for European policymakers and the European Social Fund. Recent governmental measures, such as the Youth Guarantee, the European Partnership for Apprenticeships, and Smart Specialization, reflect increased concern and efforts to promote youth skills, engagement, employability, and enterprises' financing and training capabilities. Therefore, The study aims to evaluate the policy approaches and their implementations for integrating Youth into the EU labor market. Following the conceptual research approach, this study reviewed 26 research papers from different secondary data sources and the authors used their own research experiences and insights to analyze the contemporary policies for youth integration in European countries. At the same time, this research attempts to review the impacts of the youth guarantee in EU countries and the financial disparities between policy and implementation for youth integration in the EU labor market. Finally, some recommendations are added at the end to improve the situation. Keywords: Youth Integration, Labor Market, European Union, Youth Unemployment